Applicability of Natural Gums for the Development of Controlled Release Vancomycin Hydrochloride Tablets in Site Specific Colon region using Statistical Optimization - Venkateshwarlu, K. (Asian Journal of Pharmaceutics (AJP), 2019)
The present study was initiated to develop colon targeted enteric-coated matrix tablets of Vancomycin HCl 500 mg by incorporating chitosan-based polyelectrolyte complex (PEC). The matrix tablets were development and optimized using 32-full factorial design. The Vancomycin HCl is an antimicrobial substance used in the treatment of enterocolitis. Hence, localization of the drug at its site of action is more useful. The pharmacokinetic parameters of drug also offer feasibility for colon-specific drug delivery and were developed with a view to have lag time 4–6 h, controlled release in the colon over a period of 16–20 h. The optimized formulation showed 10% drug release during lag time, 98% at 20 h, and the study of antibacterial activity for the developed best formulation indicating effective killing of Staphylococcus aureus. The study was carried out to check the ability of PEC to release the Vancomycin HCl in the presence of rat cecal content medium resembling the physiological environment of colon.